Optimal path routing in WMNs: HGAB3C based approach. (29th July 2021) - Aneja, Rattan Deep; Bindal, Amit Kumar; Kumar, Shakti
This paper proposes a new hybrid, optimal cost based routing approach namely HGAB3C implemented for routing in wireless mesh networks (WMNs). We used this proactive routing approach to find the optimal paths in dynamically created WMN of client nodes. The performance of proposed approach was evaluated with different architectural scenarios from 1000 nodes to 10, 000 nodes WMNs with a step increase of 1000 nodes. The route costs were evaluated using integrated link cost (ILC) measure which is a function of jitter, network delay and throughput. Performance of this proposed approach was compared with seven other soft computing based approaches and two hard computing based algorithms. The proposed approach outperformed all the other 9 competing approaches. The proposed algorithm can also be used effectively in isolation wards of COVID-19 hospitals and quarantine centers where robots can be networked for communications between patients and doctors.